2013
DOI: 10.1155/2013/341302
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Markers of Oxidative Stress and Antioxidant Status: Influence of External Factors

Abstract: Abstract.BACKGROUND: Salivary markers of oxidative stress and antioxidant status represent promising tool for the research of oral diseases. One of the criteria is the validation of these biomarkers from the perspective of the confounding and modifying factors. AIM: To examine the effect of circadian rhythm, tooth-brushing and ascorbic acid treatment on selected salivary markers of oxidative and carbonyl stress, and antioxidant status. SUBJECTS AND METHODS: Whole unstimulated saliva samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 46 publications
2
53
0
2
Order By: Relevance
“…The salivary EBC thiobarbituric acid reactive substances (TBARs) can be affected by the entire respiratory tract from the oral cavity to the alveolar. A study conducted by Hodosy & Celec (2005) using 19 healthy subjects found that the concentration of salivary TBARs was significantly higher in the morning, plus a study by Kamodyová et al (2013) also found that the salivary TBARs were higher in the morning, yet without statistical significance. Thus, when collecting the EBC to study the oxidative and lipid peroxidation biomarkers, the diurnal variation should also be considered.…”
Section: Discussionmentioning
confidence: 96%
“…The salivary EBC thiobarbituric acid reactive substances (TBARs) can be affected by the entire respiratory tract from the oral cavity to the alveolar. A study conducted by Hodosy & Celec (2005) using 19 healthy subjects found that the concentration of salivary TBARs was significantly higher in the morning, plus a study by Kamodyová et al (2013) also found that the salivary TBARs were higher in the morning, yet without statistical significance. Thus, when collecting the EBC to study the oxidative and lipid peroxidation biomarkers, the diurnal variation should also be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, none of the previous studies has identified whether the salivary levels of GR are linked with the degree of periodontal breakdown in terms of extent/severity or their association with different periodontal conditions 14,17,19,20 . Because saliva has gained significant recognition as a biologic sample for the detection of biochemical and cellular markers related to oxidative stress and alveolar bone loss, 21–23 this study aims to compare the concentration of GR in unstimulated whole saliva from individuals with AgP or CP and healthy controls (HCs), as well as elucidate its association with the periodontal clinical status.…”
mentioning
confidence: 99%
“…Dissimilarity between FRAP and TAC results might originate from the fact that FRAP assay measures mainly non‐protein TAC, whereas the TAC assay developed by Erel 37 . also measures antioxidative effect of proteins 52 . Plasma FRAP level was found to be lower in CsA GO+ group than in CsA GO− and H groups.…”
Section: Discussionmentioning
confidence: 93%